Miss - Namara Daphne (UCU, 2024)
The subject of this study, "The Impact of Sustainable Practices on Logistics Efficiency in Uganda," is Maersk's domestic logistics operations. The specific goals are to find out how eco- driving training practices affect logistics companies' efficiency, evaluate the impact of telematics as a fuel monitoring tool on logistics companies' efficiency, and investigate the role of stakeholder engagement in logistics companies' efficiency. A mixed-methods strategy was used, integrating some quantitative data with qualitative interviews. In a cross-sectional analysis, primary data were obtained from Maersk logistics and supplementary retrospective data were collected from archives. The study comprised fifty pertinent stakeholders, and Krejcie and Morgan's approach was used to calculate the sample size of forty-eight. Utilizing stratified and purposive sample techniques, information was gathered via questionnaires. Tables were used to present the results. The study found that although Maersk has put sustainable management practices in place, there is still room for improvement in terms of stakeholder participation throughout the supply chain, technology integration for sustainability, and mobile fuel monitoring systems. Key findings highlighted that eco-driving training positively impacted fuel efficiency and reduce emissions, while telematics significantly improved fuel monitoring and resource- optimization. However, gaps were found in consistent application across different fleet segments, and in the engagement of stakeholders, which limited the overall impact of these practices. Emergency response and access to remote areas within the distribution channels also remained challenging, affecting logistics efficiency. In conclusion, the study underscores the importance of eco-driving, telematics, and stakeholder engagement in enhancing logistics efficiency. It also identifies gaps in implementation, particularly in fleet-wide adoption and stakeholder involvement, and recommends the need for organized efforts to close these gaps to further improve logistics efficiency and sustainability in Uganda